098 Injury risk in school children with probable developmental coordination disorder or attention deficit hyperactivity disorder. (3rd March 2020) - McCallum, Kyle; Tan, Benjamin; Marjoram, Rebecca; McKay, Carly; Doyle-Baker, Patricia K; Jarus, Tal; Dewey, Deborah; Emery, Carolyn
Abstract : Background: Sport and recreation-related (S&R) injury burden is high in adolescents (ages 13–19; incidence proportions (IP) ranging 29.4–40.2 injuries/100 students/year). There is a paucity of S&R injury data in children (<13 years). Individuals with Developmental Coordination Disorder (DCD) and/or Attention Deficit Hyperactivity Disorder (ADHD) may have a higher risk of injury; however, the focus has not been S&R injury or children in these studies. Objective: To examine S&R injury risk in school children, comparing typically developing children to those screening positive for probable (p) DCD and/or ADHD. Design: Cross-sectional study. Setting: Elementary schools in Calgary, Canada. Patients (or Participants): In total, 681 students (grades 4–6; ages 8–13) from 33 randomly selected schools were recruited. Interventions (or assessment of risk factors): Children were screened for pDCD and/or pADHD through the DCD Questionnaire (DCDQ'07) and the Vanderbilt ADHD Rating Scale (VADPRS), respectively. Main outcome measurements: S&R participation and one-year injury history (medical attention and time loss) were child/parent/guardian reported on a survey. Results: The overall S&R IP was 28.2 injuries/100 participations (95%CI: 24.8–31.6). The injury rate (IR) was 2.43 injuries/1000-participation hours (95%CI: 2.06–2.85), with no significant differences between typically developing children and those screening positive for pDCD and/or pADHD. The IR for typically developing children was 2.2 injuries/1000-hours (95%CI: 1.79–2.68), 3.13 (95%CI: 2.21–4.42) for pDCD, 2.82 (95%CI: 1.29–5.34) for pADHD, and 2.93 (95%CI: 1.52–5.12) for children with pDCD and ADHD. Compared to typically developing children, children with pDCD [adjusted odds ratio (OR) =1.08; 95%CI: 0.64–1.84], pADHD (OR=1.14; 95%CI: 0.53–2.45), and pDCD/ADHD (OR=1.24; 95%CI: 0.58–2.65) were at no greater risk for S&R injuries. Conclusions: Similar to adolescents, burden of S&R injury is high in children. Children with pDCD and/or pADHD were not at a greater risk of S&R injury than typically developing children. Injury prevention strategies should target children and adolescents.